2005
DOI: 10.1093/jurban/jti021
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Diversity Among Black Men Who Have Sex with Men in an Inner-City Community

Abstract: Dramatic increases in HIV-incidence rates have been documented for Black men who have sex with men (MSM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 25 publications
5
65
3
4
Order By: Relevance
“…Although concentrated groups of high-risk male populations with bisexual behavior and heterosexual identity have not been identified in many cultures and communities, they are known to exist. Examples of these are often the populations described as being "on the down low" in US culture (Miller, Serner, & Wagner, 2005;Millett, Malebranche, Mason, & Spikes, 2005), and while being "on the down low" does not necessarily equate to a marginalized population, the lack of bisexual identification and the compartmentalization and separation of their homosexual behavior from their heterosexual behavior is reminiscent of the esquineros' behaviors. Other work in Latino populations in the United States and in other Latin American countries also reflects this type of population, even though specific pockets of these groups have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Although concentrated groups of high-risk male populations with bisexual behavior and heterosexual identity have not been identified in many cultures and communities, they are known to exist. Examples of these are often the populations described as being "on the down low" in US culture (Miller, Serner, & Wagner, 2005;Millett, Malebranche, Mason, & Spikes, 2005), and while being "on the down low" does not necessarily equate to a marginalized population, the lack of bisexual identification and the compartmentalization and separation of their homosexual behavior from their heterosexual behavior is reminiscent of the esquineros' behaviors. Other work in Latino populations in the United States and in other Latin American countries also reflects this type of population, even though specific pockets of these groups have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Although past research on bisexually identified and behaviorally bisexual men has been conducted among ethnic and racially diverse samples, the existing research on non-gay identified MSMW is limited by its exclusive focus on African American (Lichtenstein, 2000;Martinez & Hosek, 2005;Miller, Serner, & Wagner, 2005;Wheeler, 2006) and Latino men (Finlinson, Colon, Robles, & Soto, 2006;Munoz-Laboy & Dodge, 2005;Williams, Wyatt, Resell, Peterson, & Asuan-O'Brien, 2004). Although bisexual behavior, non-gay identification, and non-disclosure of same-sex behavior are more common among African American and Latino men than among White non-Hispanic men Kennamer, Honnold, Bradford, & Hendricks, 2000;McKirnan, Stokes, Doll, & Burzette, 1995;Montgomery, Mokotoff, Gentry, & Blair, 2003;Rietmeijer, Wolitski, Fishbein, Corby, & Cohn, 1998;Ross et al, 2003), research indicates that a substantial number of White men are also non-gay identified, non-disclosing, and bisexually active (Earl, 1990;Goldbaum, Perdue, & Higgins, 1996;Weatherburn, Hickson, Reid, Davies, & Crosier, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This clearly documents the need for better strategies to motivate BMSM to use HIV counseling and testing services. The need to conduct stringent studies on HIV prevention and facilitators to HIV testing among BMSM has never been more timely (Miller, Serner, & Wagner, 2005).…”
mentioning
confidence: 99%